The antifungal activity of essential oil extracted from Melaleuca alternifolia against pathogenic fungi on mango (Mangifera Indica L.) for mango postharvest application - Nagoor Gunny, Ahmad Anas; Anak Seminai, Jenny Janam; Che Mat, Mohd Hishamuddin; Ahmad, Abdul Aziz; Yusof, Rizana; Abdullah, Fadhilnor (Trans Tech Publications Ltd, 2022)
An infection by pathogenic fungi is one of the major problems in post-harvest stage of mangoes. Therefore, the extraction of essential oil from Melaleuca alternifolia is being tested as a natural fungicide for controlling fungus infections of selected mangoes locally known as susu mango. The extraction was performed using Solvent-Free Microwave Assisted Extraction with a yield of 0.57% concentration. The inhibitory effect of this essential oil against isolated fungi from mango was investigated through in-vitro and in-vivo analyses. Distilled water was used as a negative control while chemical fungicide (Globus 5.5) was used as a positive control in the analyses. The mycelial growth inhibition of the extracted essential oil for poisoned food test and disc diffusion method showed 62.50 +- 0.49% and 59.70 +- 0.30%, respectively, for in-vivo experiment which used unwounded and artificially wounded mangoes. The result also demonstrated that the essential oil applied on the mangoes could decrease the disease incidence from 100% to 61.33% for up to 10 days incubation at room temperature compared to that of the control. Hence, the essential oil of Melaleuca alternifolia can act as a green fungicide and is also a promising alternative to the synthetic chemical fungicide for controlling post-harvest disease on mangoes.